Krajobraz jadalny w prozie polskiej XXI wieku – próba typologii - Roszczynialska, Magdalena (Przestrzenie Teorii, 2025)
The article characterizes one of the non-visual approaches to landscape – the edible landscape. The term, introduced to describe home gardens combining aesthetic and utilitarian values, is treated by the author as a starting point for identifying landscapes where the cultural component is weakened in favor of the environmental one. The author uses the concept of ecosystem services and tracks how provisioning, supporting, and regulatory functions are realized in the landscape. In the first part of the article, the author presents research tools (new materialism, dark ecology, ecosystem services). Edible landscapes are interpreted as practices of “hacking the Anthropocene” – deconstructing agrologistics techniques. In the second part of the article, the author creates a typology of edible landscapes present in 21st-century Polish prose, which includes: the landscape of consumption, edible mnemotopos, terroir, urban garden. The author considers the works of D. Słowik, M. Lebda, J. Fiedorczuk, M. Płaza, Ł. Barys, K. Fedorowicz, A. Muszyński, Ł. Łuczaj, M. Książek. The edible landscape is considered as an adequate way of literary manifestation of nature in the Anthropocene era, and at the same time, in the form of urban gardening, an intervention practice aimed at socio-environmental justice. Consequently, the edible landscape is seen as a landscape enabling survival in the face of ecological catastrophe. At the same time, the environmental/climatic profile of early 21st-century Polish prose is noted.